A state of ophthalmology in ancient Rome - Bieganowski, Lech (Klinika Oczna / Acta Ophthalmologica Polonica, 2004)
The article presents the state of medical knowledge of the peoples forming Etruscan and Roman civilization circa 600 years B. C. Medical practices of these peoples are discussed. It is underlined that some Etruscan views were adopted by the Romans who caed much about hygiene. However, the development of Roman medicine was stricly related to the Greek And Egiptian physicians to this country. Various conditions of ophthalmic inflammation and many ocular diseases like pterygium, entropionand tumor of the lids were knownn in the Roman society. We owe to Celsus the description of the couching of the catarct. Oculists could be find in military hospitals (valetudinarias), and the navy. However, some civilian physicians like Antyllus – a famous surgeon who also performed the couching of the cataract, and Rufus of Ephesus – an author of a great descriptionof the anatomy of the eye ae still remembered.